The Development of a Network of Primary Care Services. - บุญเจียร, ปราโมทย์ (Journal of Preventive Medicine Association of Thailand, 2018)
The development of a network of primary care services in Muang District, Loei Province. Objective is to developing primary health care network to be accepted, wanted, appreciated from patients and people. The development were modeled on Result Based Management, Participatory, Performance and Continuous Quality Improvement. The project have started since 2013-2015, had 3 phases 1) Situation analysis 2) Network service system development 3) Evaluation, data analysis and problem has been occurred Situation analysis of our services system there were 11 focus areas: 1) Continuity of Management 2) Information Technology 3) Relationship between staffs in Loei Hospital and Primary Care Team 4) Non-communicable Diseases service system 5) Acute care service system 6) Infectious control system 7) Support system about medicine and medical equipment 8) Referral and continuous of care system 9) Human Resource Management 10) Budget 11) Community participation In reviewing nearly 3 years experienced with this plan. We generally found the following: All of the various health care team worked better together in order to delivery better health care, found more efficient ways to manage medical equipment, established a better continuous of care system (COC), patient expressed a high level of satisfaction with these implemented improvements